Phenomenon of the Rise of Sharia Tourism: A Case Study in Central Java Great Mosque - Muthoifin Muthoifin; Dimas Setyo Fathoni (International Journal of Halal System and Sustainability, 2022)
The purpose of this research is to find out, describe, analyze and reveal the causes of the rise of sharia tourism among the people of Central Java which is currently a phenomenon and to find out whether the Grand Mosque of Central Java has met the criteria as an organizer of sharia tourism. This type of research uses field research (field research). The approach used is a qualitative approach that is juridical-sociological. Data collection methods are through interviews, documentation, direct field observation and documentation. The occurrence of the phenomenon of sharia tourism in Central Java has happened a long time ago, with the many tombs of the guardians making religious tourism develop rapidly in Central Java. Islamic community culture is also an important cause of the rise of sharia tourism in Central Java, in other words, the Islamic community in Central Java demands that all aspects of life do not violate Islamic religious norms. The concept of sharia tourism is an actualization of the concept to Islam where the values of halal and haram are the main benchmarks. As for the factors that cause sharia-based tourism in addition to fulfilling spiritual needs, the development of tourist object destinations, today the factors of sharia tourism which have a wider scope such as outdoor tourism, museum tours, artificial tourism and mosques that have a unique architecture are the cause. the increasing number of sharia tourism in the community. Nowadays a mosque is not only a place of worship for Muslims but also a place that has multiple functions such as an attractive tourist destination, architectural beauty and history, which attracts people during their visits to mosques with historical and architectural stories. The Grand Mosque of Central Java, located in the city of Semarang, is a mosque that organizes sharia-based tours, has many facilities that match the criteria as a sharia-based tourist attraction. There are many objects that can be visited when it comes to the Great Mosque of Central Java, which of course has strict regulations for visitors who come to stay within the corridor of sharia in organizing it as a tourist attraction. By weighing 3 (three) elements, namely access, attractions and facilities, the Grand Mosque of Central Java has met the criteria as an organizer of sharia-based tourism objects.